LANGUAGE STYLE IN THE NOVEL DARADASIH BY SUDIBJO Z. HADI SUTJIPTO - Sa’diyah, Ngalimatus; Zulaifah, Siti; Rosanto, Dipta (Jurnal Ilmu Bahasa, Sastra dan Pengajarannya, 2023)
This study aims to describe the types of language styles contained in the novel Daradasih by Sudibjo Z. Hadi Sutjipto. The research theory uses the theory of language style proposed by Tarigan and Keraf. The research data collection technique uses library techniques, namely by reading, recording data and also calculating the observed data. In data analysis techniques, content analysis techniques are used. From the discussion of the problems in this study, it is found that there are seven language styles used in the novel Daradasih, namely simile, personification, metonymy, synecdoke, allusion, metaphor, and sarcasm. The functions of the seven language styles in Daradasih’s novel are simile language style functions to compare; personification language style functions to associate inanimate objects like humans; metonimia language style functions as a characteristic or name of things linked to people as a substitute; synecdoke language style functions to state the whole or state for part; allusion language style functions to know the events that occur; metaphor language style functions to compare in a short form; sarcasm language style functions to satirize or mock the very ugly.